Tendering process / Nur Afifah Syahril - Syahril, Nur Afifah (Universiti Teknologi MARA UiTM,Perak, 2022)
Open tender is one of the types of tenders in Malaysia and tender document is one of the essential things before proceeding with the project. The aim of this research is to study as well as prepare the tender document without small mistakes. The data used in the study was collected from the observation, interviews and document review. The findings show that there are a lot of documents that needed to be attached along with the tender document before submitting and if fail to do so the tender might get rejected. The understanding about the tender and staff’s favour really helps with the success of submitting tender document without any problem before the dateline.